Panretinal-Photocoagulation before Pars Plana Vitrectomy Influences Vitreous Level of Interleukin-6 but not of Vascular Endothelial Growth Factor in Patients with Diabetic Retinopathy - Shimura, Masahiko (Master Publishing Group, 2007)
For eyes with diabetic retinopathy which require vitreous surgery and pan-retinal photocoagulation (PRP), pre-treatment of PRP before vitreous surgery reduce the activity of diabetic retinopathy, however sometimes cause macular edema leading to visual disturbance. Some cytokines in the vitreous increase in eyes with diabetic macular edema, thus the relationship between PRP and vitreous cytokines is to be investigated. In this study, 72 eligible eyes of 65 patients were recruited, and 36 eyes had pre-treatment of PRP before vitreous surgery. The other 36 eyes were served as control which had PRP not before but under surgery. There was no statistical significant difference of systemic conditions between two groups. All eyes had pars plana vitrectomy, and 1 ml of vitreous sample was obtained under the surgery. Vascular endothelial growth factor (VEGF) and interleukin-6 (IL-6) in the vitreous sample were measured in each case. After the completion of pre-treatment of PRP, macular edema defined as increase of foveal thickness was prominently worsened, and the vitreous level of IL-6 in PRP pre-treated group showed statistically higher than that in control. In contrast, there was no significant difference of VEGF level between two groups. While, vitreous level of VEGF in control group was strongly correlated with grade of retinopathy and duration of diabetes. In conclusion, PRP influenced vitreous level of IL-6 but not VEGF, leading to macular edema, which suggests that IL-6 plays critical roles of PRP induced macular edema.